2018
DOI: 10.1021/acs.jpcb.8b05975
|View full text |Cite
|
Sign up to set email alerts
|

Instrumental Effects in the Dynamics of an Ultrafast Folding Protein under Mechanical Force

Abstract: The analysis and interpretation of single molecule force spectroscopy (smFS) experiments is often complicated by hidden effects from the measuring device. Here we investigate these effects in our recent smFS experiments on the ultrafast folding protein gpW, which has been previously shown to fold without crossing a free energy barrier in the absence of force (i.e., downhill folding). Using atomic force microscopy (AFM) smFS experiments, we found that a very small force of ∼5 pN brings gpW near its unfolding mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 35 publications
0
19
1
Order By: Relevance
“…Linkers stretched at a finite force (F) can even create an entropic barrier not present in the absence of applied force (15,16). More generally, there is an expanding set of theoretical and experimental studies (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) investigating how such instrumental and assay parameters affect the underlying biomolecular dynamics and whether the measured dynamics are dominated by the instrument used to measure them.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Linkers stretched at a finite force (F) can even create an entropic barrier not present in the absence of applied force (15,16). More generally, there is an expanding set of theoretical and experimental studies (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) investigating how such instrumental and assay parameters affect the underlying biomolecular dynamics and whether the measured dynamics are dominated by the instrument used to measure them.…”
mentioning
confidence: 99%
“…Historically, limited force precision and stability coupled with the slow response of the force probe has made it challenging to perform AFM-based equilibrium and near-equilibrium studies (32) and thereby difficult to quantify the role of instrumental artifacts. Recent work using a standard gold-coated cantilever concluded that the equilibrium dynamics of the fast-folding protein gpW were dominated by the dynamics of the cantilever diffusing on a force-induced entropic barrier (29). Such results raise significant concerns about interpreting rates or landscapes measured in AFM studies of globular protein folding and thereby motivate the following question: How do variations in intrinsic protein folding dynamics manifest in AFM-based studies, particularly in an experimental regime dominated by an instrument-induced entropic barrier?…”
mentioning
confidence: 99%
“…FRET experiments generally have yielded even faster transition path times (Chung et al, 2012 ; Chung and Eaton, 2013 ). However, timescales are not directly comparable between different experimental techniques, because of the time-limiting effect of the measurement apparatus (Cossio et al, 2015 , 2018 ; De Sancho et al, 2018 ). The best-characterized system in optical tweezers, DNA hairpins, generally displays much faster transitions than proteins (Neupane et al, 2016 ), likely because their transitions, owing to the experimental unzipping geometry, are well-described by a one-dimensional diffusion model (Neupane et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Here we employ single molecule magnetic tweezers [14][15][16][17] , which enable (i) capturing of the unfolding/refolding trajectories of the same single protein over extended (hour-long) periods of time with high stability 15 , (ii) under a wide range of constant forces (2-100pN), (iii) in passive clamp mode (hence avoiding potential masking of the protein fluctuations due to the active electronic feedback 18 ), (iv) in the absence of long tethers (which necessarily add additional inherent fluctuations to the protein construct 19 ), and, most importantly, (v) in an experimental set-up where the measured stiffness is dominated by the intrinsic stiffness of the protein-of-interest (and not the pulling device, such as e.g. the AFM cantilever [20][21][22] , Fig. S1 and SI text) to capture the change in compliance upon mechanical unfolding/refolding of individual proteins, in both monomeric and polymeric forms.…”
Section: Introductionmentioning
confidence: 99%